IMPROVING SOCIAL MEDIA LITERACY TO COLLEGE STUDENTS ABOUT COVID-19 HEALTH PROTOCOLS THROUGH VIRTUAL CLASSROOMS - Haris, Risma; Suriati, Suriati; Rahmawati, Rahmawati; Indrawati, A.; Warda, Warda; Rizal, Faisal (Universitas Muhammadiyah Mataram, 2021)
Abstract:Â This community service (PKM) focuses on improving students' social media literacy skills through virtual classroom-based learning at PPs UIT Public Health. This determination of increasing social media literacy skills is motivated by the low level of social media literacy skills and information media design among students. In addition, the massive spread of Covid-19 protocol information in the community as well as the new phenomenon of social media users that increased during the pandemic. The goals achieved by this PKM: 1) improve social media literacy skills and information media design among students through virtual classroom-based learning activities 2) invite social media design practitioners as guest lecturers to share knowledge, 3) provide work experience for lecturers and students, 4) design the covid-19 health protocol information media. The method used is through lectures and demonstrations. Demonstration related materials were delivered through interactive dialogue. Furthermore, it is carried out with media design practices and uploaded to social media. This PKM produces health promotion product outcomes. Some of the components that have been achieved include: 1) achievement of the goals of PKM activities, 2) achieving the target material that has been compiled, 3) producing a media design for the Covid-19 health protocol information which is then shared on social media.Abstrak: Pengabdian kepada masyarakat (PKM) ini berfokus pada peningkatan keterampilan literasi media sosial mahasiswa melalui pembelajaran berbasis virtual classroom di Kesehatan Masyarakat PPs UIT. Penentuan peningkatan kemampuan literasi media sosial ini dilatarbelakangi oleh masih rendahnya kemampuan literasi media sosial dan desain media informasi di kalangan Mahasiswa. Selain itu, penyebaran informasi protokol covid-19 dimasyarakat yang masif serta fenomena baru pengguna media sosial yang meningkat di masa pandemi. Tujuan yang dicapai PKM ini : 1) meningkatkan kemampuan literasi media sosial dan desain media informasi di kalangan mahasiswa melalui kegiatan pembelajaran berbasis virtual classroom 2) mendatangkan praktisi desain media sosial sebagai dosen tamu untuk sharing ilmu, 3) memberikan pengalaman kerja untuk dosen dan mahasiswa, 4) membuat desain media informasi protokol kesehatan covid-19. Metode yang digunakan adalah melalui ceramah dan demonstrasi. Materi-materi terkait demonstrasi disampaikan melalui dialog interaktif. Selanjutnya dilaksanakan dengan praktik desain media dan diupload ke media sosial. PKM ini menghasilkan outcome media promosi kesehatan. Beberapa komponen yang berhasil dicapai diantaranya: 1) ketecapaian tujuan kegiatan PKM berdasarkan evaluasi terlaksana 70%, 2) tercapainya target materi yang telah susun berdasarkan evaluasi terlaksana 75%, 3) menghasilkan desain media informasi protokol kesehatan Covid-19 yang selanjutnya dishare ke media social berdasarkan evaluasi terlaksana 90%.